Dynamic response of road tunnel subjected to internal Boiling liquid expansion vapour explosion (BLEVE) - Cheng, R.; Chen, Wensu; Hao, Hong; Li, J. (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
During service life, road tunnels may face threats of accidental explosions, e.g., Boiling Liquid Expansion Vapour Explosions (BLEVEs) due to accidents of vehicles transporting hazardous goods inside the tunnels. However, very limited study has investigated the influence of BLEVEs inside a tunnel on its dynamic response. The present study numerically investigates the dynamic response of an arched tunnel subjected to an internal BLEVE by using the software LS-DYNA. The BLEVE load is directly simulated by using commercial code FLACS or approximated by the commonly used TNT equivalency method to investigate the influences of loading predictions on the tunnel responses. The results show that the corner and upper arc of arched lining are more prone to be damaged under the directly predicted BLEVE loads. Compared to the directly predicted BLEVE loads, explosion loads estimated by the TNT equivalency method induce more significant damage to the lining due to its higher peak pressure, but smaller peak displacements since the corresponding impulse is lower than that of the BLEVE load. In addition, parametric studies are conducted to investigate the effects of concrete grade, concrete thickness, steel reinforcement ratio, and stiffness of surrounding rock mass on dynamic response of the arched tunnel subjected to the internal BLEVE. It is found that increasing concrete grade and thickness and enhancing the stiffness of surrounding rock mass are more effective than increasing steel reinforcement ratio in improving the performance of the arched tunnel against internal BLEVE loadings.